Jurnal UMKM Bengkel Motor Speedzone Garage - Sultan Ikram Al Afi; M Agung Hermawan; Novadilastri Novadilastri; Sularno Sularno (CV. ITTC INDONESIA, 2025)
The development of the automotive sector in Indonesia has driven rapid growth in supporting industries such as motorcycle repair shops, which play a crucial role in supporting community activities. This study aims to analyze the profile, management strategy, and business challenges and opportunities of Speed ​​Zone Garage—a motorcycle repair shop offering vehicle service, maintenance, and modification services in Padang City, West Sumatra. The research method used was a descriptive qualitative case study approach. Data were collected through interviews, field observations, and documentation. Analysis was conducted using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results indicate that Speed ​​Zone Garage excels in terms of service quality, experienced mechanics, and complete and modern facilities. However, the business still faces several obstacles, including suboptimal promotion and an unstrategic workshop location. A SWOT analysis reveals that Speed ​​Zone Garage has significant growth opportunities through strengthening its digital promotion strategy, improving human resource competencies, and partnering with motorcycle communities. Implementing strategies that adapt to developments in automotive technology, such as fuel-injected and electric motorcycles, is crucial for maintaining competitiveness in the future. This study concludes that Speed ​​Zone Garage's success depends not only on technical excellence, but also on managerial skills, service innovation, and a customer-oriented marketing strategy. Keywords: Motorcycle repair shop, Speed ​​Zone Garage, business analysis, development strategy, automotive services.